PADU as a Transformative Pillar: Advancing Inclusive Access and Skill Development - Shafira Zulfa Ramadhani; Qadri Karim; Nindya Duta Sari (Prospect: Jurnal Pemberdayaan Masyarakat, 2025)
The lack of inclusive spaces for interaction often leads to the social exclusion of persons with disabilities and limits their access to opportunities for self-development. Komunitas Tuli Peduli Bitung, through the Pusat Ajar Disabilitas Unggul (PADU) program, aims to address this issue by providing an accessible and empowering learning environment. This program is designed to enhance the skills and independence of persons with disabilities through need-based training such as sign language, souvenir production, and other vocational skills. The empowerment approach is participatory and collaborative, involving beneficiaries in every stage of the process—from identifying needs to evaluating outcomes. Activities are carried out through classroom learning, focus group discussions, and guided mentoring based on observation. The results show improvements in participants’ individual capacities, self-confidence, and the development of more inclusive social interactions between persons with and without disabilities. PADU contributes to strengthening social and economic inclusion and offers potential for cross-sector collaboration in the empowerment of vulnerable groups